Thermophysical Properties of Vegetable Oil-Based Hybrid Nanofluids Containing Al2O3-TiO2 Nanoparticles as Insulation Oil for Power Transformers - Wanatasanappan V.V.; Rezman M.; Abdullah M.Z. (MDPI, 2023)
The massive demand in the electrical power sector has resulted in a large demand for reliable, cost efficient, and environmentally friendly insulation oil to reduce the dependency on mineral oil. The hybridization of nanoparticles in vegetable oil is a novel method to enhance the thermal properties of vegetable oil. This study focuses on the experimental investigation of the thermophysical properties of coconut oil, soybean oil, and palm oil-based hybrid nanofluids suspended with Al2O3-TiO2 nanoparticles at a mass concentration of 0.2, 0.4, and 0.6%. The ratio between Al2O3 and TiO2 nanoparticles was maintained constant at 50:50. The main purpose of the study is to evaluate the thermal conductivity, dynamic viscosity, and density of different vegetable base oils suspended with Al2O3-TiO2 in the temperature range of 30 to 60 C. The influence of temperature on the augmentation of thermophysical properties for different vegetable oil-based hybrid nanofluids is investigated experimentally. The experimental results for thermal conductivity for the three types of base fluids show that the effect of nanoparticle mass concentration in thermal conductivity enhancement is less significant for temperatures more than 50 C. The palm oil with a 0.6% Al2O3-TiO2 nanoparticle concentration exhibited the highest thermal conductivity with a 27.5% thermal conductivity enhancement relative to the base oil. The effect of nanofluid temperature on density and viscosity augmentation is more distinct compared with the impact of Al2O3-TiO2 nanoparticles concentrations. Among all three types of hybrid nanofluids, palm oil based nanofluids were found to have superior thermophysical properties compared with coconut oil and soybean oil, with the highest thermal conductivity of 0.628 W/mk and lowest viscosity of 17.772 mPas. 2022 by the authors.